IMPLEMENTASI POSISI SEMI FOWLER PADA PASIEN CONGESTIVE HEART FAILURE (CHF) DENGAN GANGGUAN POLA NAPAS DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Fidia Nurul Khafizah; Nina Fentiana; Ika Ariyanti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Congestive Heart Failure (CHF) is a complex syndrome characterized by impaired ventricular function in pumping blood, leading to symptoms such as shortness of breath. This study aims to describe the implementation of the semi-Fowler's position in CHF patients with ineffective breathing patterns. This research used a descriptive case study design, carried out through nursing care stages including assessment, diagnosis, intervention, implementation, and evaluation, along with observation sheets andphysical examinations. The study was conducted on two respondents at TK II Putri Hijau Hospital, Medan. The results showed an improvement in oxygen saturation (Sp02) in both patients after the semi-Fowler 's position was applied. In the first patient, Sp02 increased from 95% to 97%, while in the second patient, it increased from 94% to 98%. The findings indicate that the semi-Fowler's position helps improve respiratory quality and increase oxygen saturation in CHF patients. This intervention is recommended as an easily implemented non-pharmacological nursing approach for inpatient care. Nurses are encouraged to apply this intervention for CHF patients.